A Rare Case of a Primary Unilateral Low-Grade Paratesticular Leiomyosarcoma in a 2 Years Old Dog - Balao da Silva, Carolina; Gómez Gordo, Luis; Cuesta Gerveno, Jesús María; Ortega-Ferrusola, Cristina; Martín-Muñoz, Patricia; Duque Carrasco, Francisco Javier; Parejo, Carlos; Peña Vega, Fernando (Frontiers in Veterinary Science, 2019)
A two years old dog was brought to the clinic with complains of testicular enlargement. The tissue was diffusely affected as confirmed by ultrasonographic examination, being the right testicle atrophied and the right epididymis enlarged, with loss of echotexture and presence of several anechogenic areas. The situation required the excision of the referred testicle and epididymis. Final diagnose made by histopathological analysis was primary unilateral low-grade paratesticular leiomyosarcoma. Scarce bibliography is found on this matter, with several cases reported on human, and none in dog. This case report is therefore an important milestone on the area of small animal oncology directly related to the reproductive tissue.